Wettability Gradient-Induced Diode: MXene-Engineered Membrane for Passive-Evaporative Cooling - Lei, Leqi; Meng, Shuo; Si, Yifan; Shi, Shuo; Wu, Hanbai; Yang, Jieqiong; Hu, Jinlian (Nano-Micro Letters, 2024)
Thermoregulatory textiles, leveraging high-emissivity structural materials, have arisen as a promising candidate for personal cooling management; however, their advancement has been hindered by the underperformed water moisture transportation capacity, which impacts on their thermophysiological comfort. Herein, we designed a wettability-gradient-induced-diode (WGID) membrane achieving by MXene-engineered electrospun technology, which could facilitate heat dissipation and moisture-wicking transportation. As a result, the obtained WGID membrane could obtain a cooling temperature of 1.5 °C in the “dry” state, and 7.1 °C in the “wet” state, which was ascribed to its high emissivity of 96.40% in the MIR range, superior thermal conductivity of 0.3349 W m−1 K−1 (based on radiation- and conduction-controlled mechanisms), and unidirectional moisture transportation property. The proposed design offers an approach for meticulously engineering electrospun membranes with enhanced heat dissipation and moisture transportation, thereby paving the way for developing more efficient and comfortable thermoregulatory textiles in a high-humidity microenvironment. Highlights: 1 Engineering MXene into electrospun nanofibers can effectively enhance its thermal emissivity and conductance, and the unidirectional water transport of the wettability-gradient-induced-diode (WGID) membrane displayed diode-like properties with wettability gradient by tailoring the water contact angle of each single layer. 2 The WGID membrane could achieve a cooling temperature of 1.5 °C in the “dry” state, and 7.1 °C in the “wet” state, with high emissivity of 96.40% in the MIR range, superior thermal conductivity of 0.3349 W m−1 K−1. 3 Zero-energy-consumption for personal cooling management via multiple heat dissipation pathways, including thermal radiation, conduction, and evaporation.